2021
DOI: 10.31925/farmacia.2021.3.9
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Methylphenidate Hydrochloride Combined With Platycladi Seed Extract on Attention Deficit Hyperactivity Disorder in a Murine Model

Abstract: The study aimed to evaluate the therapeutic effect and the underlying mechanism of methylphenidate hydrochloride combined with Platycladi seed extract on attention deficit hyperactivity disorder (ADHD) in a murine model. Forty-eight SPF male SHR rats were divided into 4 groups as follows: a rat model of attention deficit hyperactivity disorder that received 10 mL/kg bw/day saline solution, a methylphenidate hydrochloride group treated with 3.75 mg/kg bw/day methylphenidate hydrochloride, a Platycladi seed extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 21 publications
2
2
0
Order By: Relevance
“…To investigate the effect of KD on brain nervous system, we determined the effect of KD on the expression of neurotransmitters, including biogenic amines 5-HT and NE, and their downstream G protein effectors and second messengers, such as AC and cAMP, respectively [ 22 ]. ELISA analysis of brain tissues showed that the concentrations of 5-HT, NE, AC, and cAMP were significantly lower in SHR than WKY rats ( Fig 2A ), which is consistent with other studies [ 23 , 24 ]. Moreover, compared with the ND group, a significant boost in the concentrations of 5-HT, NE, AC, and cAMP in the MPH and KD group were observed, both in SHR and WKY rats ( Fig 2A ).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…To investigate the effect of KD on brain nervous system, we determined the effect of KD on the expression of neurotransmitters, including biogenic amines 5-HT and NE, and their downstream G protein effectors and second messengers, such as AC and cAMP, respectively [ 22 ]. ELISA analysis of brain tissues showed that the concentrations of 5-HT, NE, AC, and cAMP were significantly lower in SHR than WKY rats ( Fig 2A ), which is consistent with other studies [ 23 , 24 ]. Moreover, compared with the ND group, a significant boost in the concentrations of 5-HT, NE, AC, and cAMP in the MPH and KD group were observed, both in SHR and WKY rats ( Fig 2A ).…”
Section: Resultssupporting
confidence: 92%
“…In our study, the concentrations of 5-HT, NE, AC, and cAMP of SHR in the KD group were strikingly higher than that in the ND group. These results are consistent with previous two studies [ 23 , 24 ]. Moreover, we also proved that the expressions of DRD1, DAT, cAMP, PKA, and DARPP32 were upregulated after KD treatment.…”
Section: Discussionsupporting
confidence: 94%
“…Attention deficit hyperactivity disorder (ADHD) is an increasingly common neurodevelopmental disorder, characterized by motor hyperactivity, attention deficit disorders, distraction, impulsive behavior, learning disorders along with problems in relationships with others (Figure 1) (Belousova, 2003;J. H. Zhao et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Attention deficit hyperactivity disorder (ADHD) is an increasingly common neurodevelopmental disorder, characterized by motor hyperactivity, attention deficit disorders, distraction, impulsive behavior, learning disorders along with problems in relationships with others (Figure 1) (Belousova, 2003; J. H. Zhao et al, 2021). It affects approximately 8%–12% of children worldwide (Luo et al, 2019), with ~2–3 million children have been diagnosed in the United States (Brue & Oakland, 2002).…”
Section: Introductionmentioning
confidence: 99%